(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Nano crystalline ceramic PbSrCaCuO was prepared by the solid state technique via a high-energy ball milling process through mechanically assisted synthesis.The prepared sample was then subjected to calcinations to acquire the desired homogeneity and phase formation. To establish the elemental composition EDX analysis was done.TGA and DTA were used to study the behaviour of the sample upon heating to a high temperature.